Expression profile of G-protein βγ subunit gene transcripts in the mouse olfactory sensory epithelia - Sathyanesan, Aaron; Feijoo, Adrian A.; Mehta, Saloni T.; Nimarko, Akua F.; Lin, Weihong (Frontiers in Cellular Neuroscience, 2013)
Heterotrimeric G-proteins mediate a variety of cellular functions, including signal transduction in sensory neurons of the olfactory system. Whereas the Gα subunits in these neurons are well characterized, the gene transcript expression profile of Gβγ subunits is largely missing. Here we report our comprehensive expression analysis to identify Gβ and Gγ subunit gene transcripts in the mouse main olfactory epithelium (MOE) and the vomeronasal organ (VNO). Our reverse transcriptase PCR (RT-PCR) and realtime qPCR analyses of all known Gβ(β1,2,3,4,5) and Gγ(γ1,2,2t,3,4,5,7,8,10,11,12,13) subunits indicate presence of multiple Gβ and Gγ subunit gene transcripts in the MOE and the VNO at various expression levels. These results are supported by our RNA in situ hybridization (RISH) experiments, which reveal the expression patterns of two Gβ subunits and four Gγ subunits in the MOE as well as one Gβ and four Gγ subunits in the VNO. Using double-probe fluorescence RISH and line intensity scan analysis of the RISH signals of two dominant Gβγ subunits, we show that Gγ13 is expressed in mature olfactory sensory neurons (OSNs), while Gβ1 is present in both mature and immature OSNs. Interestingly, we also found Gβ1 to be the dominant Gβsubunit in the VNO and present throughout the sensory epithelium. In contrast, we found diverse expression of Gγ subunit gene transcripts with Gγ2, Gγ3 and Gγ13 in the Gαi2-expressing neuronal population, while Gγ8 is expressed in both layers. Further, we determined the expression of these Gβγ gene transcripts in three post-natal developmental stages (p0, 7 and 14) and found their cell-type specific expression remains largely unchanged, except the transient expression of Gγ2 in a single basal layer of cells in the MOE during P7 and P14. Taken together, our comprehensive expression analyses reveal cell-type specific gene expression of multiple Gβ and Gγ in sensory neurons of the olfactory system.